GELIOADSORPTION SYSTEM OF HEAT AND COOL SUPPLY - Draganov, B. (Енергетика і автоматика, 2016)
Shows the basic characteristics of adsorption termotransformator. The analysis of circuit design of heat and cool supply based gelioadsorption and heat accumulation systems.